The Past is Prologue: Telling our Stories about Textbook Affordability Programs - Shirkey, Cynthia; Hoover, Jeanne K.; Anderson, Serin; Parker, Suzan (My University, 2017)
Conversations about textbook affordability and open educational resources are gaining traction and visibility across the nation with advocacy by student groups, state legislators, and leaders in higher education. Responding to this need, library textbook programs continue to evolve. In this Lively Lunch, presenters will lead a dynamic discussion on the impact of textbook programs on students and libraries. Over twenty five years ago, the two branch campus libraries of the University of Washington took fundamentally different approaches to providing access to textbooks. The UW Bothell Library cultivated a robust textbook course reserve program by proactively purchasing all required texts, while the UW Tacoma Library opted for a more restrictive approach. Today, both libraries have modified their textbook programs: the UW Bothell Library is now focusing on higher use / higher cost items, while the UW Tacoma Library is launching a new textbook purchasing program. Both libraries are expanding programs focused on affordable alternatives and open educational resources. Historically, Joyner Library at East Carolina University has not purchased assigned textbooks due to high cost and the speed with which editions go out of style. However, Joyner Library has been actively growing its textbook affordability initiatives over the past 2 years. Their programs have focused on purchasing multi-user e-books and developing a mini-grant program for faculty to construct classes using OER instead of traditional textbooks. Bring your lunch and join us for a lively discussion on textbook affordability programs ranging from purchasing textbooks to identifying and creating open educational resources. We will discuss the impact and role of textbooks on collection development policies and budgets, as well as the impacts on our users. We will also talk about open textbooks as an emerging area that may require additional librarian training. We are particularly interested in sharing best practices and innovative strategies that discussion participants are using to create their own textbook initiatives.
Presented at the 2017 Charleston Conference, Charleston, South Carolina.
Keywords: Textbook Affordability; Collection Development; Scholarly Communication; Textbooks